"Members of the University of Pennsylvania Museum junior modeling class" (Philadelphia Evening Bulletin, 1930)
Members of the University of Pennsylvania Museum's junior modeling class reproduce miniature relics of past civilizations. Dorothy Anne Smith revives a modern Inuit village on a miniature scale under the supervision of Miss Florence Musselman, director of the Realistic Modeling Class. Title from clipping caption